The Influence of Physical Fitness on Attempt to Enhance Student’s Concentration in Physical Education Learning - Ai Faridah; Dian Permana; Arief Adhitia Hamzah; Dimas Andyka Putra (Universitas Majalengka, 2024)
Physical fitness is the ability of a person's body to perform physical activities properly and efficiently. To determine the influence of physical fitness on an attempt to enhance students' concentration in physical education learning at UPTD State Elementary School 2 Kutamanah. The sample in this study amounted to 42 students at UPTD State Elementary School 2 Kutamanah taken using a disproportionate stratified random sampling technique. This study uses a quantitative approach with experimental research methods and pre-experimental design research design with pre-test and post-test design types. The independent variable in this study is physical fitness, while the dependent variable is concentration. In this study, the grid concentration exercise test was used to test concentration. Statistical calculations using SPSS 25 paired sample t-test. The data processing shows that the significance value of (0.00) <0.05, then H_0 is rejected and H_1 is accepted, which means that physical fitness influences an attempt to enhance student concentration in PE learning at state elementary school 2 Kutamanah. Therefore, physical fitness is crucial for students' concentration, and researchers interested in researching physical fitness are advised to develop it further.